A K‐band self‐biased sextupler with enhanced harmonic suppression using quasi‐lumped bandpass filters. Issue 7 (27th February 2019) - Tian, Yaoling; Chen, Fengjun; Jiang, Jun; Huang, Kun; He, Yue
Abstract: A K‐band harmonic suppression enhanced sextupler with a chip dimension of 3 × 1 mm 2 using the 0.13 μm GaAs MHEMT process is presented. The configuration of the sextupler consists of two transistors and two quasi‐lumped bandpass filters. From the measured results, the conversion loss of the sextupler is 3‐7 dB from the frequency range of 20.6‐26.3 GHz without any additional amplifier. The fourth harmonic, fifth harmonic, seventh harmonic, eighth harmonic, and ninth harmonic show rejection over 28‐60, 34‐43, 12‐41, 25‐65, and 20‐49 dBc, respectively.